Impaired mnemonic pattern separation associated with PTSD symptoms paradoxically improves with regular cannabis use - Jacob Ross; Bruna Cuccurazzu; Dylan Delmar; Christian Cortez; Giovanni Castillo; Dean T. Acheson; Dewleen G. Baker; Victoria B. Risbrough; Daniel M. Stout (npj Mental Health Research)
Abstract Posttraumatic stress disorder (PTSD) is associated with poor hippocampal function and disrupted pattern recognition. Cannabis use is highly prevalent in individuals with PTSD, yet the impact on these cognitive functions is poorly understood. Participants (n = 111) with a range of PTSD symptoms with and without regular cannabis use completed the mnemonic similarity task. We hypothesized that regular use would be associated with alterations in pattern separation ability in individuals with PTSD symptoms. High PTSD symptoms were associated with reduced pattern separation performance in minimal users. Regular users with high PTSD symptoms showed greater pattern separation, but reduced pattern separation with low PTSD symptoms. These results suggest that regular cannabis use may disrupt pattern separation and similar hippocampal-dependent processes, while it may improve pattern separation in individuals with high PTSD symptoms. These cross-sectional results require longitudinal follow-up studies to evaluate the causal effects of regular cannabis use on cognitive function in PTSD.